2015
DOI: 10.1007/s13312-015-0741-8
|View full text |Cite
|
Sign up to set email alerts
|

Shanghai fever: A fatal form of Pseudomonas aeruginosa enteric disease

Abstract: Early detection and management of complications of P. aeruginosa enteric disease is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Gross inspection of the intestinal lesions in our case revealed extensive circular perforations with red, crater-shaped protrusions. Histopathology indicated infiltration of a large number of acute and chronic inflammatory cells, with hyperplasia of granulation tissue, inflammatory exudative necrosis, and extravasation of red blood cells, which was consistent with previous reports [4,5] and highlighted that the intestinal lesions occurred as a consequence of blocked arteries caused by thrombi or bacterial embolization. The patient's condition was critical when vascular occlusion caused intestinal tissue necrosis, accompanied by infection leading to neutrophil infiltration and abscess formation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Gross inspection of the intestinal lesions in our case revealed extensive circular perforations with red, crater-shaped protrusions. Histopathology indicated infiltration of a large number of acute and chronic inflammatory cells, with hyperplasia of granulation tissue, inflammatory exudative necrosis, and extravasation of red blood cells, which was consistent with previous reports [4,5] and highlighted that the intestinal lesions occurred as a consequence of blocked arteries caused by thrombi or bacterial embolization. The patient's condition was critical when vascular occlusion caused intestinal tissue necrosis, accompanied by infection leading to neutrophil infiltration and abscess formation.…”
Section: Discussionsupporting
confidence: 91%
“…A case with ecthyma gangrenosum combined with multiple perforations of the small intestine associated with P. aeruginosa was reported in Japan, where a 13-month-old boy presented with several episodes of watery diarrhea, pyrexia, and irritability [4]. Halder et al [5] reported a case of a 9month-old baby girl with P. aeruginosa enteric disease who acted irritable since the onset of the fever. An emergency abdominal surgery was performed to repair 5 perforations of the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…PCA showed that opportunistic pathogen from genera Pseudomonas and Pantoea were main bacterium community that drive the cluster of H5N1 infectious individuals, and symbionts in genera Mycoplasma moatsii and Halomonas contributed to the cluster of healthy controls. It is reports that genus Pseudomonas infections could occur in the skin, blood and lungs, and some species of genus Pantoea could result in soft tissue or joint infections (Cruz et al, 2007 ; Smith et al, 2014 ; Halder et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa is an opportunistic gram‐negative bacillus found in the environment, especially water. Pseudomonas exotoxins disrupt protein synthesis, host cell cytokeratin, block phagocytosis and cause cell death 1,2,5 . Four exotoxins, ExoU, ExoS, ExoT and ExoY and their determining genes have been identified.…”
Section: Discussionmentioning
confidence: 99%